2015
DOI: 10.1002/oby.21048
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue is associated with microstructural brain tissue damage

Abstract: Our data indicate that increased abdominal VAT rather than SAT is associated with microstructural brain tissue damage in elderly individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
6
24
1
Order By: Relevance
“…42 These latter mechanisms could have contributed to our results, given that visceral obesity is linked to higher circulating IL6 and high-sensitivity CRP, indicating lowgrade systemic inflammation. 9,44 Our study supports these findings and indicates, by means of mediation path analyses, that visceral obesity increases the development of dWMHs through increases in inflammatory activity, indexed by circulating IL6. 9,44 Our study supports these findings and indicates, by means of mediation path analyses, that visceral obesity increases the development of dWMHs through increases in inflammatory activity, indexed by circulating IL6.…”
Section: Underlying Mechanismssupporting
confidence: 82%
See 1 more Smart Citation
“…42 These latter mechanisms could have contributed to our results, given that visceral obesity is linked to higher circulating IL6 and high-sensitivity CRP, indicating lowgrade systemic inflammation. 9,44 Our study supports these findings and indicates, by means of mediation path analyses, that visceral obesity increases the development of dWMHs through increases in inflammatory activity, indexed by circulating IL6. 9,44 Our study supports these findings and indicates, by means of mediation path analyses, that visceral obesity increases the development of dWMHs through increases in inflammatory activity, indexed by circulating IL6.…”
Section: Underlying Mechanismssupporting
confidence: 82%
“…20,43 Interestingly, studies comparing subcutaneous with visceral adipose tissue not only revealed a higher association with inflammatory markers for visceral adipose tissue, but also correlated specifically central obesity (ie, a higher amount of visceral fat) with microstructural brain damage. 9,44 Our study supports these findings and indicates, by means of mediation path analyses, that visceral obesity increases the development of dWMHs through increases in inflammatory activity, indexed by circulating IL6. For CRP, we observed a similar tendency, which did not reach statistical significance.…”
Section: Underlying Mechanismssupporting
confidence: 82%
“…Much of the focus has been on visceral adiposity (Debette et al, 2010; Widya et al, 2015) due to the accompanying metabolic derangements of insulin resistance, hypertension, and pro-inflammatory and pro-thrombotic states. These likely relate to the release of adipokines and inflammatory cytokines, including interleukin-6 and TNFα, and by altered free fatty acid metabolism in the portal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on the role of blood pressure implicates loss of brain tissue in the frontal and temporal lobes (Beauchet et al, 2013;Schneider et al, 2017). Another study reported that it is visceral adipose tissue that appears to be tied to microstructural changes in the brain (Widya et al, 2015). Another study reported that it is visceral adipose tissue that appears to be tied to microstructural changes in the brain (Widya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A casecontrol comparison of people with and without metabolic syndrome reported reduced white matter, in addition to gray matter (Sala et al, 2014). Another study reported that it is visceral adipose tissue that appears to be tied to microstructural changes in the brain (Widya et al, 2015). Typically, these MVRFs co-occur in people, requiring precise physiological endpoints and large samples to disentangle their effects.…”
Section: Introductionmentioning
confidence: 99%